Understanding Interactions between Social Security Claimants and Frontline Employment Advisers - Public and Private Provision in the UK - Merran Toerien; Roy Sainsbury; Paul Drew; Annie Irvine (Social Work & Society, 2015)
This paper reports findings from the first study based on recordings of advisory interviews with benefits claimants in the United Kingdom.  Previous econometric analysis found that programmes for unemployed people delivered through private sector Employment Zones (EZs) were more effective than their public sector equivalents, delivered through Jobcentre Plus (JCP).  However, little was known about what occurred on the frontline.  In this paper, we describe a conversation analytic comparison of 40 EZ and 48 JCP interviews, showing that EZ and JCP advisers typically adopted different 'interactional styles'.  We illustrate the five features that characterised the EZ 'style', arguing that they offer an important part of the explanation for the EZs' outperformance of some JCP programmes.  Given their systematic patterning, we also argue that these differences are not best explained at the individual level.  Nevertheless, we conclude that there is no principled reason for the practices identified in the EZ to be considered to 'belong' in the private, but not the public, sector.